Interventions to standardise hospital care at presentation, admission or discharge or to reduce unnecessary admissions or readmissions for patients with acute exacerbation of chronic obstructive pulmonary disease: a scoping review. Issue 1 (1st December 2020) - MacDonell, Rachel; Woods, Orla; Whelan, Stephanie; Cushen, Breda; Carroll, Aine; Brennan, John; Kelly, Emer; Bolger, Kenneth; McNamara, Nora; Lanigan, Anne; McDonnell, Timothy; Prihodova, Lucia
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease that may be punctuated by episodes of worsening symptoms, called exacerbations. Acute exacerbations of COPD (AECOPD) are detrimental to clinical outcomes, reduce patient quality of life and often result in hospitalisation and cost for the health system. Improved diagnosis and management of COPD may reduce the incidence of hospitalisation and death among this population. This scoping review aims to identify improvement interventions designed to standardise the hospital care of patients with AECOPD at presentation, admission and discharge, and/or aim to reduce unnecessary admissions/readmissions. Methods: The review followed a published protocol based on methodology set out by Arksey and O'Malley and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Electronic database searches for peer-reviewed primary evidence were conducted in Web of Science, EMBASE (Elsevier) and PubMed. Abstract, full-text screening and data extraction were completed independently by a panel of expert reviewers. Data on type of intervention, implementation supports and clinical outcomes were extracted. Findings were grouped by theme and are presented descriptively. Results: 21 articles met the inclusion criteria. Eight implemented a clinical intervention bundle at admission and/or discharge; six used a multidisciplinary care pathway; five used coordinated case management and two ran a health coaching intervention with patients. Conclusion: The findings indicate that when executed reliably, improvement initiatives are associated with positive outcomes, such as reduction in length of stay, readmissions or use of health resources. Most of the studies reported an improvement in staff compliance with the initiatives and in the patient's understanding of their disease. Implementation supports varied and included quality improvement methodology, multidisciplinary team engagement, staff education and development of written or in-person delivery of patient information. Consideration of the implementation strategy and methods of support will be necessary to enhance the likelihood of success in any future intervention.